Alien Monstrosity: The Practice of Technology and “Race” as Technological Construct in Star Trek: Voyager - Nils Jablonski (European Journal of American Studies)
Alongside class, gender and age, race as an elementary category in modern science fiction is particularly apparent in the Star Trek franchise. The television series Star Trek: Voyager (USA 1995–2001) presents race as a cultural construct that depends on the specific depiction of technology and how it is used. This article analyzes several episodes of Voyager in order to explore how the series connects alien otherness with a certain practice of technology. It is this practice that determines the extent of the aliens’ monstrosity; this practice either conforms with or deviates from the humanist values associated with technology and its use. Calling the universality of these values into question, the series presents a specifically posthuman depiction of race as technological construct.